Capital-skill complementarity and the redistributive effects of social security reform - Casarico, Alessandra,Devillanova, Carlo (Univ., Center for Economic Studies [u.a.], 2003)
This paper analyses the general equilibrium implications of reforming pay-as-you-go pension system in an economy with heterogeneous agents, human capital investment and capital-skill complementarity. It shows that increasing funding delivers in the long run higher physical and human capital and therefore higher output, but also higher wage and income inequality. The latter affects preferences over the degree of redistribution of e remaining pay-as-you-go component: despite the greater role that edistribution could perform in the new steady state, we find a preference for lower redistribution for a larger group of the population.
Internetausg.: http://www.cesifo.de/pls/ifo_app/DocLinkCESifoDl?getDoc=cesifo1_wp1038.pdf
Keywords: Arbeitspapier; Graue Literatur; Rentenfinanzierung; Umlageverfahren; Gesetzliche Rentenversicherung; Faktorsubstitution; Theorie; Verteilungswirkung